Correlation between Gunung Padang and Sundanese Traditional Roof - Nadia Absharina Idris; Adinda Putri Maharani; Miftah Tri Nur Fauzi; I Putu Wijaya THomas Brunner (REKA KARSA)
Abstract Gunung Padang is the oldest prehistoric megaliths in Indonesia which has a function as a place of worship for the people who settled there about 2000BC according to its orientation and philosophy. Meanwhile after dark ages, people knowledge on building shelter arises therefore many traditional houses are build and had their philosophy implemented such as the vertical and horizontal beliefs in relation of human, nature, and divinity. This study concerns architecture identity correlation of place in the two eras because of cultural transition which can be observed until now. Gunung Padang has a similar vertical concept identity compare to Sundanese traditional roof according to both philosophy if the highest place is the most sacred place and describes the relationship between human, nature and divinity. The purpose of this study is to examine the correlation between Gunung Padang and the Sundanese traditional roof concept in religion and cultural aspect. Qualitative methods that leverages vernacular theory is used of the analysis methods.     Key Words: Gunung Padang, identity, Sundanese traditional roof.